Studi Operasional antara Penghimpunan dan Penyaluran Dana di BSI KCP Kediri Bandar - Salsabila, Zakiya; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2025)
This study examines the operational balance between fund mobilization and financing distribution at Bank Syariah Indonesia (BSI) KCP Kediri Bandar, which relocated in late 2024 from the Universitas Islam Kadiri (Uniska) area to the western side of the Brantas River. The analysis focuses on fundraising strategies through savings, current accounts, and deposits, as well as financing schemes tailored to the needs of the surrounding community. The findings reveal that BSI KCP Kediri Bandar has effectively implemented fundraising strategies through products such as Special Profit-Sharing Deposits, Rezeki Berkah program, Pesta Hadiah program, and Easy Mudharabah Savings. On the financing side, the bank mainly focuses on vehicle financing and Mitraguna financing with civil servant decree (SK) collateral, reflecting the actual needs of the majority of its customers. The balance between fund mobilization and financing distribution not only ensures financial stability but also demonstrates the social role of Islamic banking in fostering local economic growth. Hence, the operations of BSI KCP Kediri Bandar embody Islamic principles of fairness, transparency, and adaptability to community dynamics.